User-centered development of a smartphone application (Fit2Thrive) to promote physical activity in breast cancer survivors. Issue 2 (16th August 2021) - Welch, Whitney A; Solk, Payton; Auster-Gussman, Lisa; Gavin, Kara L; Whitaker, Madelyn; Cullather, Erin; Izenman, Emily; Courneya, Kerry S; Ackermann, Ronald; Spring, Bonnie; Cella, David; Penedo, Frank; et al.
Abstract: Increased moderate and vigorous physical activity (MVPA) is associated with better health outcomes in breast cancer survivors; yet, most are insufficiently active. Smartphone applications (apps) to promote MVPA have high scalability potential, but few evidence-based apps exist. The purpose is to describe the testing and usability of Fit2Thrive, a MVPA promotion app for breast cancer survivors. A user-centered, iterative design process was utilized on three independent groups of participants. Two groups of breast cancer survivors (group 1 n = 8; group 2: n = 14) performed app usability field testing by interacting with the app for ≥3 days in a free-living environment. App refinements occurred following each field test. The Post-Study System Usability Questionnaire (PSSUQ) and the User Version Mobile Application Rating Scale (uMARS) assessed app usability and quality on a 7- and 5-point scale, respectively, and women provided qualitative written feedback. A third group ( n = 15) rated potential app notification content. Quantitative data were analyzed using descriptive statistics. Qualitative data were analyzed using a directed content analysis. The PSSUQ app usability score ( M 1 = 3.8; SD = 1.4 vs. M 2 = 3.2; SD = 1.1; lower scores are better) and uMARS app quality score ( M 1 = 3.4; SD = 1.3 vs. M 2 = 3.4; SD = 0.6; higher scores are better) appeared to improve in Field Test 2. Group 1 participants identified app "clunkiness, " whereas group 2 participants identified issues with error messaging/functionality. Group 3 "liked" 53% of the self-monitoring, 71% of the entry reminder, 60% of the motivational, and 70% of the goal accomplishment notifications. Breast cancer survivors indicated that the Fit2Thrive app was acceptable and participants were able to use the app. Future work will test the efficacy of this app to increase MVPA. Abstract : "Increasing time spent in moderate-to-vigorous physical activity is associated with better health outcomes in breast cancer survivors. Even so, most breast cancer survivors do not meet current physical activity recommendations for moderate-to-vigorous physical activity. One potential solution to assist breast cancer survivors in increasing their physical activity is to provide remote access to a physical activity promotion intervention through a smartphone application (app). Our purpose was to describe the iterative process we completed to design, Fit2Thrive, a moderate-to-vigorous physical activity promotion app for breast cancer survivors. We recruited three separate groups of survivors to test app components and provide feedback on the useability and app quality, with updates being made to the app between each test group. At the end of this iterative design process, breast cancer survivors indicated that the Fit2Thrive app was acceptable, and participants were able to use the app. Our future work will test the efficacy of the app to increase moderate-to-vigorous physical activity among breast cancer survivors."